The long shadow of Vinuya in the time of artificial intelligence reflections on ethical issues in legal research - Tamase, Paolo S. (Philippine Law Journal, 2023)
Artificial intelligence ("AI") has permeated all industries, the legal profession being no exception. Amid apprehensions concerning the use of generative AI, this Essay revisits the Vinuya saga to demonstrates how the Court's decision to redefine plagiarism by requiring intent and its contemporaneous actions that undermined the legal academy has affected legal research ethics well into the age of AI. The essay then argues for efficiency-based reasons to prohibit plagiarism as originally and widely understood, with the end goal of seeing generative. AI as a tool that can be used for justice instead of a threat to academic integrity.